Penguatan Pendidikan Karakter Bagi Siswa SMK Negeri 3 Gorontalo - Wantu, Asmun W.; Hamim, Udin; Adjie, Zulfikar; Mustafa, Febrianti (Penerbit Widina, Widina Media Utama, 2025)
This study aims to address the declining trend of students’ character values through a collaborative character education strengthening program at SMK Negeri 3 Gorontalo. Technological advancement, while offering convenience, also poses a risk of eroding students’ moral values. The research employed a collaborative approach involving lecturers, students, and school stakeholders, consisting of three phases: preparation (needs analysis, coordination, and material development), implementation (socialization, seminars, and interactive discussions), and evaluation through surveys and feedback. The results indicate a considerable improvement in students’ understanding of core character values such as honesty, responsibility, and discipline, along with active participation in reflective activities. The program also strengthened the synergy between schools and higher education institutions as a foundation for sustainable character development. The study concludes that collaborative and contextual approaches are effective in instilling character values, although periodic evaluations are necessary to ensure long-term internalization. These findings emphasize the importance of integrating character education throughout the entire educational ecosystem, both at the school and university levels.ABSTRAKPengabdian ini bertujuan untuk mengatasi tren penurunan nilai-nilai karakter pada siswa melalui program penguatan pendidikan karakter berbasis kolaborasi di SMK Negeri 3 Gorontalo. Kemajuan teknologi, meski membawa kemudahan, juga berpotensi menggerus nilai-nilai karakter siswa. Metode yang digunakan adalah pendekatan kolaboratif antara dosen, mahasiswa, dan pihak sekolah, yang meliputi tiga tahap: persiapan (analisis kebutuhan, koordinasi, dan penyusunan materi), pelaksanaan (sosialisasi, seminar, dan diskusi interaktif), serta evaluasi melalui survei dan umpan balik. Hasil pengabdian menunjukkan peningkatan pemahaman siswa terhadap nilai-nilai karakter, seperti kejujuran, tanggung jawab, dan kedisiplinan, serta partisipasi aktif dalam kegiatan reflektif. Program ini juga memperkuat sinergi antara sekolah dan perguruan tinggi sebagai fondasi penguatan karakter berkelanjutan. Kesimpulan pengabdian ini menegaskan bahwa pendekatan kolaboratif dan kontekstual efektif dalam menanamkan nilai-nilai karakter, meskipun memerlukan evaluasi berkala untuk memastikan internalisasi jangka panjang. Temuan ini mendukung pentingnya integrasi pendidikan karakter dalam seluruh ekosistem pendidikan, baik di tingkat sekolah maupun perguruan tinggi.